Litteraturens brugspotentiale. Peter Seebergs “Patienten” læst som en sygdomsfortælling - Rasmussen, Anders Juhl (Passage - Tidsskrift for litteratur og kritik, 2018)
Anders Juhl Rasmussen: “The Usability of Literature. Peter Seeberg’s “The Patient” Read as an Illness Narrative” This article examines the relationship between the uses of literature and narrative medicine. Peter Seeberg’s short story “The Patient” is interpreted as an illness narrative in relation to Ludwig Wittgenstein’s therapeutic philosophy of language. Rasmussen suggests that Seeberg’s reliance on the use of everyday language in the short story is an analogy to a new position in literary studies where criticism and engagement, rationality and emotionality are united.